Cavovarus deformity in Charcot-Marie-Tooth disease: is there a hindfoot equinus deformity that needs treatment?. Issue 1 (December 2015) - Beckmann, Nicholas; Wolf, Sebastian; Heitzmann, Daniel; Wallroth, Annika; Müller, Sebastian; Dreher, Thomas
Abstract Background Charcot-Marie-Tooth disease (CMT), one of the most common hereditary neurologic disorders, often results in debilitating cavovarus foot deformities. The deformities are still not fully understood, and the treatment recommendations are consequently heterogeneous, often including calf muscle or Achilles tendon lengthening. Methods We examined 40 patients (80 feet) with CMT and bilateral cavovarus deformities (19 men and 21 women, mean age 33.6 ± 14.6 years) and the feet of a healthy control population of 13 individuals (7 men and 6 women, mean age 43.9 ± 10.8 years). In all cases 3D instrumented gait analysis results with both conventional Plug-in-Gait analysis and the Heidelberg Foot Measurement Method (HFMM) were used to determine the sagittal plane kinematics, dorsi-plantar flexion (DPF), tibio-talar dorsiflexion (TTDF), and medial arch angle (MAA), and the results of patients and the control group were compared using the 2 methods. Decreased and increased dorsiflexion using TTDF was defined as 1 standard deviation below or above the mean of the control. Comparisons were done using descriptive statistics, the Pearson correlation coefficient and ANOVA. Results The TTDF was found to be decreased in 18 of the 80 feet examined (22.5 %), normal in 31 feet (38.75 %), and increased in 31 feet (38.75 %). The Pearson coefficient showed a positive correlation withR = 0.765, p < 0.001 between decreased TTDF values found by HFMM and decreased DPF values found with conventional Plug-in-Gait analysis, but a very weak correlation in patients with normal TTDF (R = -0.118) and increased TTDF (R = 0.078). Also, in patients with decreased TTDF values, there was a weak to moderate correlation with the MAA (R = 0.335), but no correlation between the MAA and DPF (R = 0.023). Conclusions The HFMM, unlike the conventional Plug-in-Gait analysis, distinguishes between the segments of the foot in foot deformities and facilitates evaluation of the hindfoot equinus component in patients with CMT and cavovarus deformity. Although there is a significant correlation between decreased TTDF with HFMM and decreased DPF with conventional Plug-in-Gait analysis, this correlation was not seen in patients with normal or increased TTDF values. Conventional Plug-in-Gait analysis alone does not indicate if an increased plantar flexion deformity is the result of either a cavus deformity or hindfoot equinus deformity, which limits its usefulness in assisting in treatment decision making.